Comparison of hair cortisol concentrations between self- and professionally-collected hair samples and the role of five-factor personality traits as potential moderators - Enge, Sören; Fleischhauer, Monika; Hadj-Abo, Alexander; Butt, Felix; Kirschbaum, Clemens; Schmidt, Kornelius; Miller, Robert (Psychoneuroendocrinology, 2020)
•HCC of self- and professionally collected hair samples was examined.•A between-subject (N = 482) and a within-subject sample (N = 50) was used.•No significant differences between the two hair collection methods occurred.•Personality did not moderate the influence of collection method on HCC. Cortisol concentration of hair (HCC) is an established biomarker in stress research that can provide valuable retrospective information on subjects’ long-term cortisol levels. Using a population-wide sample of in total N = 482 participants this study aimed to examine whether there are differences in HCC when participants collect the required samples by themselves with the help of a partner in domestic settings compared to professionally collected hair strands in the lab. Potential confounding factors that may affect HCC and might obfuscate the outcomes were considered. The results suggest that the two compared sample collection methods did not significantly differ from each other in terms of HCC (p = .307). A somewhat larger sample loss in the domestic setting was observed due to hair samples where HCC could not be determined (5.3 % vs. 1.8 % in the lab). Similarly, in a sample of N = 50 using a within-subjects design (Sample 2) no significant HCC differences between collection methods occurred (p = .206). In addition, potential moderating effects of personality traits of the Five-Factor-Model on the relationship between hair collection method and HCC were investigated. In Sample 1 personality data of the hair donor were available, while in Sample 2 personality data (n = 40) were available for the hair donor and the hair sample collector. Interestingly, none of the Big Five traits significantly moderated the relationship between HCC and hair collection method (all p > .20). Overall, these findings suggest that the self-collection of hair in domestic settings is a viable and economical method for measuring long-term cortisol concentrations in hair.